HUBUNGAN STATUS IMUNISASI DASAR LENGKAP DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS JATIBARU TAHUN 2025 - Amalia Ilmaniyah Azzaharani; Yati Purnama; Nur Islamyati (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2025)
Stunting remains a major global public health problem, with a relatively high prevalence in the working area of the Jatibaru Community Health Center. Inadequate basic immunization coverage is considered one of the potential risk factors contributing to this condition. This study aimed to analyze the relationship between complete basic immunization status and the incidence of stunting among toddlers. An observational analytic study with a cross-sectional design was conducted in June 2025. A total of 95 toddlers were selected using purposive sampling. Data were obtained from secondary sources in the form of medical records and analyzed using the Chi-Square test. The results demonstrated a statistically significant relationship between basic immunization status and stunting incidence (p = 0.000). Among toddlers with incomplete immunization, 85.7% experienced stunting, whereas only 18.3% of those with complete immunization were stunted. Furthermore, toddlers with incomplete basic immunization had a 26.7 times higher risk of developing stunting compared to those with complete immunization. Complete basic immunization acts as a crucial protective factor against stunting. Therefore, improving immunization coverage is essential to support optimal growth and development among toddlers in the Jatibaru Community Health Center area.